PhET Simulation sebagai Alternatif Media Pembelajaran Mata Pelajaran IPA di Sekolah Dasar untuk Meningkatkan Minat Belajar Siswa - Ara Septiana; Leah Afifah; Tian Kusumawati (Program Studi PGSD Kampus UPI di Serang, 2021)
The rapidly growing world of technology and information can provide an alternative for educators to use various learning media, one of which is Physics Education Technology (PhET). The purpose of writing this article describes PhET Simulations as an alternative learning medium for elementary school students, especially Natural Science subjects. The writing of this article uses qualitative methods with literature study techniques, namely literature research through the collection of verbal data such as articles, books, and various other scientific literature. The collected data is then analyzed inductively. PhET Simulations is an interactive simulation that can help learners understand abstract concepts in Natural Science lessons. PhET Simulations as an alternative to learning media can effectively be used to assist educators and learners in learning material and also Natural Science practicums that are abstract. By using PhET Silmulations, learners will be actively involved in the learning process, so that the material learned becomes more interesting and makes it easier for students to understand the material learned.